Introducing the Study of Life and Death Education to Support the Importance of Positive Psychology: An Integrated Model of Philosophical Beliefs, Religious Faith, and Spirituality - Phan, Huy P.; Ngu, Bing H.; Chen, Si Chi; Wu, Lijuing; Lin, Wei-Wen; Hsu, Chao-Sheng (Frontiers in Psychology, 2020)
Life education, also known as life and death education, is an important subject in Taiwan with institutions (e.g., high school) offering degree programs and courses that focus on quality learning and implementation of life education. What is interesting from the perspective of Taiwanese education is that the teaching of life education also incorporates a number of Eastern-derived and conceptualized tenets, for example, Buddhist teaching and the importance of spiritual wisdom. This premise contends then that life education in Taiwan, in general, is concerned with the promotion, fulfillment, and cherishing of quality life experiences (e.g., personal contentment, happiness). One example of life education, which resonates with other spiritual beliefs and religious faiths (e.g., Hinduism), is related to spiritual cultivation and the enlightenment of life wisdom. Our own teaching of the subject, likewise, places emphasis on the goal of teaching students to seek meaningful understanding of and appreciation for three major, interrelated components of life education: life wisdom, life practice, and life care. It has been acknowledged, to a certain degree, that life education has made meaningful contributions, such as the creation and facilitation of a civil, vibrant society, and that many Taiwanese individuals show dignity, respect for elders, and reverence for spiritual and religious faiths. For example, aside from high-quality hospice care, many Taiwanese engage in different types of benevolent acts (e.g., providing spiritual advice to someone who is dying), where possible. Life education is a beneficial subject for teaching and learning as its theoretical understanding may help individuals cope with pathologies and negative conditions and life experiences. One negative life experience, in this case, is the ultimate fate of humankind: death. Approaching death and/or the onset of grief is something that we all have to experience. How does one approach death? It is not easy feat, and of course, grief for a loved one is personal, and some of us struggle with this. We contend that spiritual cultivation and enlightenment, arising from life education, may assist us with the topic of death (e.g., the possibility of transcendence beyond the realm of life). More importantly however, from our own teaching experiences and research development, we strongly believe and rationalize that the subject of life education could, indeed, coincide with and support the paradigm of positive psychology (Seligman, 1999, 2010; Seligman and Csíkszentmihályi, 2000). Forming the premise of the present conceptual analysis article, we propose that a person’s “spiritual and enlightened self,” reflecting the convergence of three major aspects of life education (i.e., philosophical reflection, enrichment of personal well-being, and spiritual cultivation), would result in the initiation and creation of a number of virtues and positive characteristics, for example, having a positive outlook in life, having a perceived sense of spirituality, showing compassion, forgiveness, etc. These virtues and quality characteristics, from our philosophical reasoning, are equivalent to those qualities that the paradigm of positive psychology advocates for. In summary, we conceptualize that the subject of life education, from the perspective of Taiwanese education, may intertwine with the paradigm of positive psychology. A person’s spiritual and enlightened self, or his/her “holistic self,” from our rationalization, is the ultimate optimal life experience that he/she may have, enabling him/her to address the gamut of life conditions and experiences. The distinctive nature of life education in this case, as a point of summary, is that it incorporates spiritual beliefs and religious faiths (e.g., Buddhist faith), encouraging a person to seek nature and divine–human relationships, as well as to contemplate and to explore the complex nature of his/her inner self. The notion of Buddhist samsâra, for example, as “evidence” of spirituality, entailing the endless cycle of birth, rebirth, and redeath, may provide a person with hope into the afterlife. Such esoteric discourse, we contend, is positive and optimistic, allowing individuals to discard the dividing line between life and death.